Use of uterine electromyography to diagnose term and preterm labor - Lucovnik, Miha; Kuon, Ruben-Jeremias; Chambliss, Linda R.; Maner, William L.; Shi, Shao-Qing; Shi, Leili; Balducci, James; Garfield, Robert E. (Acta obstetricia et gynecologica Scandinavica, 2011)
Current methodologies to assess the process of labor, such as tocodynamometry or intrauterine pressure catheters, fetal fibronectin, cervical length measurement and digital cervical examination, have several major drawbacks. They only measure the onset of labor indirectly and do not detect cellular changes characteristic of true labor. Consequently, their predictive values for term or preterm delivery are poor. Uterine contractions are a result of the electrical activity within the myometrium. Measurement of uterine electromyography (EMG) has been shown to detect contractions as accurately as the currently used methods. In addition, changes in cell excitability and coupling required for effective contractions that lead to delivery are reflected in changes of several EMG parameters. Use of uterine EMG can help to identify patients in true labor better than any other method presently employed in the clinic.